Papuloerythroderma of Ofuji - a case report - Hassan, Iffat; Ahmad, Mashkoor; Manaan, Qazi; Hussain, Sajjad; Masood, Qazi (Journal of Pakistan Association of Dermatologists, 2016)
Papuloerythroderma of Ofuji is an uncommon skin condition seen in elderly patients characterized by pruritic eruption of infiltrating papules with sparing of large folds of skin. Very few cases have been reported in the literature and the frequent association of this rare entity with laboratory abnormalities and malignancy points towards its heterogenous nature. We report a case of papuloerythroderma of Ofuji having peripheral eosinophilia but not associated with any malignancy. Â